Menelusuri Mazhab Walisongo - Kholili Hasib (TSAQAFAH, 2015)
The background of this article is the emergence of new studies that argue about the origin of Walisongo and the school of faith (akidah) they adopted. On the other hand, historical writings about Walisongo are still dominated by many tales and legends. Eventhough the history of Walisongo is real, but if it is dominated by tales or legends, then in time it could become vague and full of doubt. Current debates about the identity of Walisongo have begun to enter the territory of academic studies. Orientalists, for instance, have their own perspectives about the subject, together with some historians of Nusantara. Different opinions about the subject are also found among the writers of the history of Nusantara. In this study, the author found that the Orientalist studies of Walisongo which conclude that they were not from Arab had some colonial motives and interests, and also some ideological backgrounds. Orientalists assume that it was the Arab is Islam. Therefore, their studies were directed to the Indian-centric framework. This orientalist politics is called notification. This movement is held by raising local Non-Muslims cultures. For example, by promoting Hindu-Buddhist culture as the national native culture and burying Islamic culture in which it was stigmatized as foreign Arab culture. In the context of this study, most Orientalists refused the fact of the Arab as the origin of Walisongo. They tend to choose the other opinion that stated that Walisongo came from India. Meanwhile, some new studies of Indonesian scholars questioned the school of faith (aqeedah) of Walisongo. Some of their finding that stated that Walisongo were Shia is still based on assumptions. This is the main reason why such studies have to be examined more carefully in this article.